Tailoring and optimization of a honey-based nanoemulgel loaded with an itraconazole–thyme oil nanoemulsion for oral candidiasis. (31st December 2023) - Sindi, Amal M.; Rizg, Waleed Y.; Khan, Muhammad Khalid; Alkhalidi, Hala M.; Alharbi, Waleed S.; Sabei, Fahad Y.; Alfayez, Eman; Alkharobi, Hanaa; Korayem, Mohammed; Majrashi, Mohammed; Alharbi, Majed; Alissa, Mohammed; et al.
Abstract: The use of essential oil–based nanoemulsions (NEs) has been the subject of extensive research on a variety of conditions affecting the oral cavity. NEs are delivery methods that improve the solubility and distribution of lipid medicines to the intended areas. Because of their antibacterial and antifungal properties, itraconazole and thyme oil–based self-nanoemulsifying drug delivery systems (ItZ-ThO-SNEDDS) were created to protect oral health against oral microorganisms. The ItZ-ThO-SNEDDS were created utilizing an extreme verices mixture design, and varying concentrations of ThO (10% and 25%), labrasol (40% and 70%), and transcutol (20% and 40%) were used. The ItZ-ThO-SNEDDS had droplet sizes of less than 250 nm, a drug-loading efficiency of up to 64%, and a fungal growth inhibition zone of up to 20 mm. The accepted design was used to obtain the ideal formulation, which contained ThO in the amount of 0.18 g/ml, labrasol 0.62 g/ml, and transcutol 0.2 g/ml. The best ItZ-ThO-SNEDDS formulation was incorporated into a honey-based gel, which demonstrated improved release of ItZ in vitro and improved transbuccal permeation ex vivo . In addition, when compared with various formulations tested in rats, the optimized loaded emulgel decreased the ulcer index. This study therefore demonstrated that the ItZ-ThO-SNEDDS could offer an effective defense against oral diseases caused by microbial infections.